Something old, something new: (re)analysis and interpretation of three Bronze Age trepanations from Croatia - Carić, Mario; Tresić Pavičić, Dinko; Mikić, Ilija; Čavka, Mislav; Cvitkušić, Barbara; Ivor Janković; Toyne, J. Marla; Novak, Mario (Anthropologie, 2020)
In this paper we present three prehistoric cases (two previously reported and one recently discovered) of trepanation from Croatia: Rudine, Bezdanjača and Jagodnjak, all dated to the Bronze Age. By using a detailed macroscopic analysis as well as radiographic imaging (x-ray and CT scanning) of the skulls, we provide a new assessment and interpretation for this type of surgical intervention during the Bronze Age. The first case was that of an adult male from the Rudine site dated to the Early Bronze Age; the second trepanation was recorded on an adult female from the Bezdanjača Cave, dated to the Middle/Late Bronze Age; the third case was observed on a juvenile cranium from the Jagodnjak site, dated to the Middle Bronze Age. All three cases exhibit several similarities: (i) all are located on the right side of the frontal bone; (ii) all three are of similar dimension/shape; (iii) in all cases all three layers of calvarium were breached; and (iv) similar techniques for trepanation procedure were used in all cases. These three crania represent the oldest cases of intentional medical interventions in the territory of modern-day Croatia, while the Jagodnjak individual is the youngest person thus far discovered with this kind of treatment in the region.
Keywords: dospělí; doba bronzová; Female; trepanace; Adult; ženské pohlaví; Adolescent; lidé; Trephining; Skull; Male; Croatia; Chorvatsko; dějiny starověku; pravěk; lebka; mužské pohlaví; mladiství; History, Ancient; Humans